Personalized medicine for reconstruction of critical-size bone defects – a translational approach with customizable vascularized bone tissue - Kengelbach-Weigand, Annika; Thielen, Carolina; Bäuerle, Tobias; Götzl, Rebekka; Gerber, Thomas; Körner, Carolin; Beier, Justus; Horch, Raymund E.; Boos, Anja (npj Regenerative Medicine, 2021)
Tissue engineering principles allow the generation of functional tissues for biomedical applications. Reconstruction of large-scale bone defects with tissue-engineered bone has still not entered the clinical routine. In the present study, a bone substitute in combination with mesenchymal stem cells (MSC) and endothelial progenitor cells (EPC) with or without growth factors BMP-2 and VEGF-A was prevascularized by an arteriovenous (AV) loop and transplanted into a critical-size tibia defect in the sheep model. With 3D imaging and immunohistochemistry, we could show that this approach is a feasible and simple alternative to the current clinical therapeutic option. This study serves as proof of concept for using large-scale transplantable, vascularized, and customizable bone, generated in a living organism for the reconstruction of load-bearing bone defects, individually tailored to the patient’s needs. With this approach in personalized medicine for the reconstruction of critical-size bone defects, regeneration of parts of the human body will become possible in the near future.
CRIS-Team Scopus Importer:2021-08-27